Islamic Intellectual Thought: Between Textual Cohesion and Critical Differentiation - Al-Hasani, Ismail (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2020)
Textual cohesion is for our thought to engage with the sacred text in a consistent manner, wherein its dimensions are consistently and harmoniously anchored in the thought of the Muslim scholar. As regards critical differentiation, it is the diverse cognitive ability of discernment. Accordingly, the “scientific-cognitive” interpretations of the exegetes primarily require a precise awareness of the differential orientation of scientific and intellectual activity. This renders the scholar's quest for constructing his thought and the formation of rules and laws to be a perpetual quest whose episodes are never completed in history. Secondly, what is necessitated is symbiotic cohesiveness between the Qur`anic verses because they are devoid of categorical indications insofar as what relates to any definitive scientific knowledge, given that scientific universal knowledge is among the plains of knowledge entailing varied and varying ideas and views.